(untitled) (ETIMA, 2021)
Abstract The largest source of renewable energy is the Sun. The energy from the Sun, called solar energy, is free, safe and least harmful to the environment. Solar energy is converted into electricity by devices based on semiconductor materials, called photovoltaics. If the production of electricity from fossil fuels is replaced by the production of electricity from sunlight there will be much lower emissions of carbon dioxide. This paper analyzes the location, solar radiation and network connection for the provided location for the photovoltaic power plant. For collecting data on solar radiation, satellite data at a specific location were used. Based on these analyzes, the technical characteristics of the photovoltaic power plant with a total installed power of 201.6 kW are dimensioned and selected. The principal scheme of the photovoltaic power plant and the scheme of the AC Junction box are drawn in the software package Edraw max. Finally, the economic and financial profitability of the photovoltaic power plant is reviewed and proven. Key words: solar energy, solar radiation, network connection, Photovoltaic Power Plant, AC Junction box, economic and financial profitability.